A Prospective Study to Detect Immune Checkpoint Inhibitors Associated With Myocarditis Among Patients Treated for Lung Cancer - Faubry, Clara; Faure, Maxime; Toublanc, Anne-Claire; Veillon, Rémi; Lemaître, Anne-Iris; Vergnenègre, Charlotte; Cochet, Hubert; Khan, Sadia; Raherison, Chantal; Dos Santos, Pierre; Zysman, Maeva (Frontiers in Cardiovascular Medicine, 2022)
Background Immune checkpoint inhibitors (ICIs) are widely used in lung cancer management. However, myocarditis, which is a rare, yet potentially severe adverse-related event associated with ICIs, could be under-reported. Objectives This study is aimed to prospectively evaluate the cumulative incidence rate of myocarditis, through systematic screening, among patients receiving ICIs for lung cancer. Methods All patients who received the first administration of ICIs for non-small cell (NSCLC) and small cell lung cancer (SCLC), between May and November 2020, in the pulmonary department of Bordeaux University Hospital, were included. Echocardiography (ECG), troponin-I, and natriuretic peptide dosages before ICIs' first administration and before each infusion were recorded. ECG and magnetic resonance imaging (MRI) were done additionally, in case of at least three times increase in troponin levels, ECG modifications, and the onset of cardiovascular symptoms. Second, if possible, coronarography than endomyocardial biopsy was assessed. The primary outcome was defined as ICIs related to myocarditis onset, while secondary outcomes included other cardiovascular events, disease-free, and overall survival. Results During the period of interest, 99 patients received their first infusion of ICIs for lung cancer (mean age 64 ± 9 years; 52 men, 67% with adenocarcinoma). Three cases of myocarditis without major adverse cardiac events (MACEs) occurred (two definite and one possible), and the mean duration between the first ICIs' administration and myocarditis onset was 144 ± 3 days. Median disease-free survival and overall survival were 169 [102; 233] days and 209 [147; 249] days, respectively. Conclusion In our study, systematic screening of myocarditis associated with ICIs leads to a more frequent incidence and a later onset than previously reported. None of them were severe. Additional prospective evidence is needed before we could adopt routine cardiac screening in unselected patients starting ICIs; however, these data shed new light on the risk of myocarditis associated with ICIs administration.